PCSK9 inhibitors in a renal transplant patient complicated with hepatitis B: A case report and literature review - Lv, Pinchao; Li, Yuxi; Wu, Lin; Weng, Haoyu; Chen, Ming; Ding, Wenhui; Li, Jianping (Frontiers in Cardiovascular Medicine, 2022)
Lipid metabolism disorders are recognized to be one of the most frequent complications of renal transplantation, while dyslipidemia and chronic kidney disease (CKD) are strong risk factors for arteriosclerotic cardiovascular disease (ASCVD). Proprotein convertase subtilisin/kexin type 9 inhibitors (PCSK9i) are novel lipid-lowering drugs, the safety and efficacy of which are yet to be confirmed in transplanted patients. There have been several small-sample studies using PCSK9i in patients after heart transplantation, while fewer cases use PCSK9i after kidney transplantation. We report a case of a renal transplant recipient complicated with hepatitis B treated with PCSK9i, which achieved a remarkable lipid-lowering efficacy, and no significant adverse effects were found during the follow-up.